The problem of cultural stereotyping in the pastoral care of a suicidal person - J. N. Ogbuanu (Acta Theologica)
Suicide is a complex phenomenon; attempts to reduce or prevent it remain a challenge. Completed suicide has a deep negative impact on society. Suicidologists estimate that suicide will negatively affect at least ten times as many people as an accidental death or sudden death from illness. This article attempts to contribute to the prevention of suicide. It explores the future of pastoral care for a suicidal person using European and African contexts. It identifies cultural stereotyping as a problem that has influenced pastoral care. It argues that an objective challenge to the stereotypes and a possible dialogue of cultures and approaches is needed. Particular reference to the culture and spirituality of the suicidal person could be proactive to pastoral care of suicidal persons in our multicultural society.